Comparative study on blasting simulation vibration reduction and field vibration reduction experiment of adjacent oil pipeline - Yi Chen; Ruichong Zhang; Lujia Liang; Yi Wang; Jiaozhong Chen; Chengyu Xie (Frontiers in Earth Science)
IntroductionYongxing Tunnel No.1’s complex geology near a buried oil pipeline on the Guizhou-Nanning high-speed route poses blasting risks. Prioritizing pipeline safety, efforts focus on minimizing vibration impacts.MethodsResearch uses numerical simulations and field tests to analyze three delay times and three spacing charge materials for vibration reduction.ResultsOptimal delay is 30 ms, yielding a 0.52 cm/s vibration velocity, 20%-29% lower than 28 ms and 32 ms. Soil is the most effective spacer, achieving 0.46 cm/s, 30.30%-22.03% lower than water and air. Field tests align with simulations.DiscussionFindings provide a reference for optimal vibration reduction and safe construction under similar conditions.